The Influence of Management Accounting Information System, Strategy, and Innovation To Operational Performance of Manufacturing Company in Entering the Era of Free Trade. - Harry Prabowo; Tresno Eka Jaya (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
The purpose of this writing is to analyze the influence of the analysis of independent variables to the dependent variable. The research was conducted by using primary data in the form of statement of questionnaire about independent variable of management accounting information system, strategy, and innovation to dependent variable that is company operational performance. The number of samples used are 24 manufacturing companies in DKI Jakarta that can be reached by researchers, this sample determination using Gay theory. Analytical method used is multiple linear regression with classical assumption test which include normality test, multicolonierity test, and heterokedastisity test. Writing results show that management accounting information system variables have an influence on the company's operational performance, the strategy has an influence on the company's operational performance and innovation has an influence on the operational performance of the company.